Two new species of the genus Thubdora Park and a new species of Ptilothyris Walsingham (Lepidoptera, Gelechioidea, Lecithoceridae) from Uganda - Park, Kyu-Tek; Aarvik, Leif (Zootaxa, 2021)
Two species of Thubdora Park (T. onsemiro Park, sp. nov. and T. elgozmanyi Park, sp. nov.) and one species of Ptilothyris Walsingham (P. galbiplatella Park, sp. nov.) are described from Uganda.